Myanmar: The impact of COVID-19 and food system responses - COVID-19 Hub (International Food Policy Research Institute, 2021)
In Myanmar, the COVID-19 pandemic and political upheaval have both had significant economic and social repercussions. CGIAR has been working with partners in the country to assess the economic impacts of the pandemic and their consequences for agrifood system (AFS) supply chains.